Analysis Of Quality Control of Defects In 500 Ml Plastic Bottle Products Using Fault Tree Analysis and FMEA Methods At PT. Berlina Tbk Pandaan - Syarifuddin, Adimas; Misbah, Achmad (Fakultas Sains dan Teknologi Universitas Islam Negeri Sultan Syarif Kasim Riau, 2023)
Industrial company PT. Berlina Tbk. currently engaged in manufacturing processing of plastic pellets into plastic packaging products. From the data the author has obtained for 1 month from 21 August to 22 September 2022, the production process at PT. Berlina Tbk. has a bottle product defect in 500 ml plastic packaging quality. From 21 August to 22 September 2023, this production resulted in 6,421 (2%) defects from the total machine production of 287,897 (100%) 500 ml plastic bottles. This study uses a qualitative descriptive method by conducting field research activities (field research), observations, and interviews and by studying books, journals, literature, and other references related to this research. The analysis used in this study is the FTA analysis (Fault Tree Analysis) and the FMEA method (Failure Mode and Effect Analysis). From the research to overcome and reduce the three most significant types of defects using the FTA (Fault Tree Analysis) method, it was found that the causes were influenced by several elements, such as workforce, machines, and materials. With the discovery of the most extensive defect, the researcher has made a proposal based on the RPN (Risk Priority Number), which is then analyzed using the FMEA (Failure Mode And Effect Analysis) method, namely the submission for dirty material defects by checking in the storage room for raw materials, then the type of dirty oil defect by checking on the compressor air section so that during the blowing process it avoids dirty oil. The proposal from the last researcher is a type of folded defect to periodically check the cutting temperature to see if there is a shorted thermocouple.